Neonatal supporative parotitis - A case report - Hussain, Shabbir; Alam, Samina Shamas; Hussain, Moeez (Pakistan Armed Forces Medical Journal, 2022)
A 9-day old male neonate was admitted for fever. He was born at term with normal antenatal records and a smooth transition from in utero to ex utero. He was febrile and had a left-sided pre auricular hot, tender, erythematous swelling and oral purulent discharge from Stensen’s duct. The septic profile was suggestive of sepsis. Ultrasonography revealed parotid gland enlargement with pus collection. Empirical antibiotics started, and parotid swelling pus drained. Culture of Pus from parotid swelling and Stensen’s duct yielded growth of Staphylococcus Aureus. According to the sensitivity report, antibiotics continued for ten days, and the patient was discharged after complete resolution of signs and symptoms.